PTH-051 Vitamin D and bone health in coeliac disease: a district general hospital experience. (23rd September 2015) - Al-Joudeh, A; Raychaudhuri, C; Srinivas, M; Ellis, R; Willemse, P J; Bardhan, K D; Basumani, P; Höroldt, B
Abstract : Introduction: Association between coeliac disease (CD) and osteoporosis is well studied but studies on osteomalacia in CD are lacking. We aimed to determine the prevalence of vitamin D deficiency in CD and its correlation with osteoporosis and osteomalacia in our patients. Methods: We checked vitamins D and B12, folate and ferritin levels in new and follow-up (FU) patients with proven CD, Calcium profile and Coeliac serology were checked at diagnosis or on annual review. DEXA scan was performed to assess for osteoporosis within 2 months of blood testing. Patients on Calcium and vitamin D or other Vitamin supplements and those on medication interfering with vitamin D metabolism were excluded. P value was calculated using Fisher exact test. Vitamin D (25 OHD) categories: deficient <25 nmol/l, insufficient 25–50 nmol/l, adequate >50 nmol/l. Results: 143 patients with confirmed CD (65 new, 78 follow-up, 31 male, median (range) age 50.51 (17–83) years; 8 Asian), 75 patients underwent a DEXA scan. A) 69 patients had suboptimal vitamin D level (13% deficient, 35% insufficient). While more common in new than FU patients (17% vs 10%), this did not reach significance (p=0.3). B) Median levels during FU were higher in men (62 vs 47 nmol/l) but not women (52 vs 54 nmol/l); there was no significant difference in deficiency or insufficiency between the sexes either at diagnosis or during FU. C) Median levels of patients >60 years were only slightly lower (52 vs 54 nmol/l). D) Median levels were higher in autumn than spring both for new and FU patients (61 vs 43 nmol/l, p=0.045). E) Median vitamin D levels for patients with T-score of >−1, −1 to −2.5 and <−2.5 were: 60, 47 and 43 nmol/l, respectively. Prevalence of Vitamin deficiency/insufficiency was higher in osteoporotic/oesteopenic patient than in those with normal Dexa scan (p=0.036). F) Only one patient had biochemical evidence of osteomalacia (Ca↓, phosphate↓, ALP↑), in addition 4 Ca↓ (2 vitamin D deficient), 2 phosphate↓ (1 vitamin D deficient), 4 ALP↑ (2 vitamin D deficient). G) Other deficiencies: B12: 15%, folate: 14%, iron (excluding 16 patients found to be coeliac on investigation of iron deficiency anaemia)—32% H) vitamin B12 and folate deficiency were similar among new and FU patients, where as iron deficiency was more common in new patients (45% vs 22%); but this did not reach statistical significance (p=0.07). Conclusion: Vitamin D deficiency/insufficiency is common in coeliac patients; it appears there is an association between vitamin D deficiency and osteoporosis that can be confirmed in our cohort. Biochemical evidence osteomalacia is not common—but may underestimate the clinical problem. Other vitamin deficiency while less prevalent are still common. Vitamin D testing should be added to the annual screen for coeliac patients.